Single nucleotide polymorphisms in C-reactive protein (CRP) predict response to adjunctive celecoxib treatment of resistant bipolar depression - Angelos Halaris; Daniel Hain; Rebecca Law; Lisa Brown; David Lewis; Maria Filip (Brain, Behavior, & Immunity - Health, 2023)
Background: Affective illness has been associated with a proinflammatory state, and it is generally accepted that the immune system plays a key role in the pathophysiology of mood disorders. Since inflammatory biomarkers are elevated in bipolar disorder, anti-inflammatory combination therapies may enhance response and reverse treatment resistance. Purpose: In the present study we investigated the possible impact of single nucleotide polymorphisms (SNPs) within the CRP gene on CRP blood levels, treatment response and level-of-stress perception in our cohort of treatment-resistant bipolar-depressed patients receiving escitalopram and celecoxib, or escitalopram and placebo, as previously reported (Halaris et al., 2020). Methods: Study design, clinical findings, and CRP blood levels have been reported previously (Halaris et al., 2020; Edberg et al., 2018). In this follow-up study we extracted DNA from blood cells collected at baseline. Genome-wide genotyping was performed for all subjects using the Infinium Multi-Ethnic Global-8 v1.0 Kit. Based on reports in the literature indicating possible associations with psychiatric conditions, ten previously reported CRP gene polymorphisms were evaluated in a preliminary analysis. We focused on rs3093059 and rs3093077 were in complete LD. Carriers were defined as those possessing at least one C allele for rs3093059, or at least one G allele for rs3093077. Additionally, we determined blood levels of the medications administered. Results: Non-carriers of rs3093059 and rs3093077 had significantly lower baseline CRP blood levels than carriers (p = 0.03). Increased rates of HAM-D17 response (p = 0.21) and remission (p = 0.13) and lower PSS-14 scores (p = 0.13) were observed in non-carriers among subjects receiving celecoxib but they did not reach statistical significance. When examining all subjects, nominally significant associations between carrier-status and remission (p = 0.04) and PSS-14 scores (p = 0.04) were observed after correcting for treatment arm. Non-carriers receiving celecoxib had the highest rates of response and remission, and the lowest stress scores. Conclusions: Carriers of the CRP SNPs may have higher baseline CRP levels, although non-carriers appear to benefit more from celecoxib co-therapy. Determination of the carrier status in conjunction with pretreatment blood CRP level measurement may contribute to personalized psychiatric practice, but replication of the present findings is needed.